STUDI ANALISIS KETERAMPILAN TEKNIK DASAR PERMAINAN BULU TANGKIS PADA SISWA PUTRA PESERTA EKSTRAKURIKULER SMP N 3 KAPONTORI - Nuzul Fitra; Saifu Saifu; Muhammad Zaenal Arwih (JOKER (Jurnal Ilmu Keolahragaan), 2020)
This study aims to determine the analysis study of basic technical skills of badminton games at the students extracurricular participants of SMP N 3 kapontori. This research is a quantitative descriptive study that analyzes of basic technical skills of badminton games at the students extracurricular participants of SMP N 3 kapontori. The method used is a survey method with tests and measurements to obtain real data. Tests and measurements are carried out by using forehand test and service ability, backhand short service, smash, and overhead lob. The population in this study were all the students who participated in extracurricular badminton games of SMP N 3 kapontori with a total of 20 students used as samples in this study. The instruments used to obtain data in this study were the forehand long service test, backhand, smash, and overhead lob in badminton game. The instrument test of long service is a tool measuring by device to measure the ability of service to high bounce up to the back the opposite of rival field (Barry and Nelson). The validity value of long service ability is 0.54 and the reliability value of long service ability is 0.77 (Barry and Nelson). The collected data needs to be analyzed so that conclusions can be drawn through the analysis process. The sequence analyzes the data obtained by recording numbers or values obtained based on the tests that have been carried out by each testee. Then the scores obtained from the service test, and smash are conversion with the grading norm table which is the skill category of each test.From the results of the analysis of short service forehand, short service backhand, smash, and overhead lob ability at badminton games on male students participated in extracurricular SMP N 3 kapontori mostly have less categories. Where the forehand short service ability is in category of decreasing than 14 students or 70%, backhand short service is in category of decreasing that is as many as 12 students or 60%, smash is in category of most decreasing as many as 13 students or 65%, and the overhead lob are in category of decreasing as many as 15 students or 75%. This study conclude that the basic technical skills of badminton games at the students extracurricular participants of SMP N 3 kapontori were in category of decreasing.